Disaster Prevention Through Environmental Management and Developing Biodiversity Conservation Areas (Case Study in the Upang River, Bangka Belitung Islands Province) - Marta, Dwi Jati (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The Upang Forest and River area in Tanah Bawah Village, Bangka Belitung Islands Province, has developed into a biodiversity conservation and ecotourism area in the last eight years, aiming to reduce the risk of natural and man-made disasters. The development of this forest and river is an effort to prevent disasters due to changes in people's lifestyle patterns, with illegal tin mining activities, logging, and monoculture plantations. This study aims to increase the knowledge capacity of the community in terms of awareness of maintaining biodiversity, preserving the environment, and disaster prevention to provide the potential for ecotourism in the Upang Forest and River area to be developed properly. This study uses a qualitative research method with data collection through observation, direct interviews with research participants, and a literature review. This study finds the development of Upang River ecotourism with the concept of biodiversity has a positive impact on the surrounding community by involving the Upang River Nature Friends Tourism Awareness Group in developing the Upang River Ecotourism Area in four activities, namely conservation, education, social and economic. The collaborative role of Bangka Flora Society and the village government through Friends of Nature Tourism Awareness Group (Pokdarwis Salam) Upang River, Youth Organization (Karang Taruna), and Village-owned Enterprise (BUMDesa) Tanah Bawah in developing ecotourism destinations can create wealth and develop sustainable environmental management so the concept of biodiversity can be implemented following existing regulations. The government's role in regulating the governance and provision of natural resources in the Upang River has been carried out in setting appropriate policies to create sustainable natural resource management as a basis for maintaining a balance between environmental sustainability.